2015
DOI: 10.2217/cer.15.37
|View full text |Cite
|
Sign up to set email alerts
|

Revascularization options in stable coronary artery disease: it is not how to revascularize, it is whether and when to revascularize

Abstract: Patients with acute coronary syndromes and severe multivessel or left main coronary artery disease have better outcomes when prompt revascularization is performed in addition to optimal medical therapy (OMT). However, in patients with stable ischemic heart disease, randomized strategy trials have revealed equipoise between initial strategies of OMT alone and OMT plus revascularization. Conducted in diverse stable ischemic heart disease patient populations and throughout the spectrum of atherosclerotic and isch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Invasive pressure wire studies have repeatedly demonstrated angiographic appearance relates poorly to ischaemia. [ 11 ] It is likely that prior studies will have included patients without ischaemia and thus revascularisation would give minimal benefit; such recruitment would dilute signals of benefit. Those studies that did seek ischaemia demonstrated only relatively limited levels of it.…”
Section: Does Ischaemia Matter?mentioning
confidence: 99%
See 1 more Smart Citation
“…Invasive pressure wire studies have repeatedly demonstrated angiographic appearance relates poorly to ischaemia. [ 11 ] It is likely that prior studies will have included patients without ischaemia and thus revascularisation would give minimal benefit; such recruitment would dilute signals of benefit. Those studies that did seek ischaemia demonstrated only relatively limited levels of it.…”
Section: Does Ischaemia Matter?mentioning
confidence: 99%
“…This includes large randomised controlled studies, such as COURAGE, BARI2D and FAME 2. [ 11 13 ] Table 1 shows a summary of the key studies from 1992 to 2020.…”
mentioning
confidence: 99%